2008
DOI: 10.1111/j.1365-2958.2008.06333.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of Bordetella pertussis iron transport system genes during infection

Abstract: SummaryTemporal expression patterns of the Bordetella pertussis alcaligin, enterobactin and haem iron acquisition systems were examined using alcA-, bfeA-and bhuR-tnpR recombinase fusion strains in a mouse respiratory infection model. The iron systems were differentially expressed in vivo, showing early induction of the alcaligin and enterobactin siderophore systems, and delayed induction of the haem system in a manner consistent with predicted changes in host iron source availability during infection. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 28 publications
3
36
0
1
Order By: Relevance
“…Expression of the Bordetella alcaligin, enterobactin, and heme receptor genes in infected mice and production of those receptors in human hosts indicate a natural state of iron starvation stress in vivo (21). In the current study, B. pertussis genes encoding the anticipated alcaligin biosynthesis and heme uptake functions, the BfeR regulator of the bfeA enterobactin receptor gene, TonB system genes, and genes encoding TonB-dependent receptors of unknown specificity showed increased transcript abundance under iron starvation conditions.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Expression of the Bordetella alcaligin, enterobactin, and heme receptor genes in infected mice and production of those receptors in human hosts indicate a natural state of iron starvation stress in vivo (21). In the current study, B. pertussis genes encoding the anticipated alcaligin biosynthesis and heme uptake functions, the BfeR regulator of the bfeA enterobactin receptor gene, TonB system genes, and genes encoding TonB-dependent receptors of unknown specificity showed increased transcript abundance under iron starvation conditions.…”
Section: Discussionmentioning
confidence: 75%
“…Similar analyses using a B. pertussis heme receptor mutant demonstrated an in vivo growth defect in the late stages of infection, suggesting that persistence in the host depends on heme utilization (24). The BfeA enterobactin receptor was required for growth of B. pertussis in the early stages of mouse infection (21). Recent studies indicated that B. pertussis upregulates expression of the alcaligin, enterobactin, and heme utilization genes in vivo, confirming that the mammalian host is an iron-restricted environment and that the cognate iron sources are likely present in the host during infection (21).…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…These do not appear to be redundant, as mutations in either feo or yfe resulted in a significant growth defect (45). Similarly, Bordetella pertussis uses different systems at different times during infection (46). The alcaligin and enterobactin siderophore systems are expressed early in the course of infection, while heme transport is induced late, reflecting the availability of different iron sources during the course of infection.…”
Section: Discussionmentioning
confidence: 99%